Discrepancy in climatic zoning of the current soil productivity evaluation system - CHUCHMA, Filip; STŘEDOVÁ, Hana (Contributions to Geophysics and Geodesy, 2015)
Pedologic-ecological estimation in the Czech Republic (Central Europe) means determination of land agronomic productivity and its economical pricing and is expressed as a five position numeral code and mapped as iso-lines. The first position of the code is the climatic region representing approximately the same conditions for agricultural plant growth and development. This climatic regionalization was based on the climatic data from 1901–1950. Currently, there is the need to update their existing zoning due to the technological progress of measurement and development of climate models including estimation of future climate. The aim of the paper is (i) to apply actual climatic data to climatic regionalization and (ii) to estimate what climatic conditions are relevant for actually valid climatic regions. The original methodology currently enables us to unequivocally classify only 17% of the entire territory of the Czech Republic (and 18% of Czech agricultural land). A substantial part of the territory does not fit neatly into individual climatic regions. Subsequently the actually valid ranges of climatic characteristics of individual climatic regions were determined. The GIS layers of individual climatic variables computed with data from 1961–2010 were one by one covered by GIS layers of individualclimatic regions based on data from 1901–1950. Interval ranges of climatic region variables determined in this way are valid for the period 1961–2010. The upper limit of air temperature sum above 10 °C and annual air temperature in most of the climatic regions was significantly shifted up in 1961–2010. An increase in precipitation is noticeable in wet climatic regions. Moisture certainty in vegetation season and probability of dry vegetation are the most problematic in terms of Estimated Pedologic-Ecological Units (EPEU) climatic zoning. This should be taken into account when fixing the official soil price.